Acceptance, Adaptation and Adoption: The key to Colombian Refugees in New Zealand Overcoming Barriers of Belonging - Lopez Severiche, Alfredo; Lopez Severiche, Alfredo; Lopez Severiche, Alfredo (Corporación Universitaria Americana, 2024)
Introduction: This article examines the barriers of integration that Colombian refugees confront in New Zealand, including culture shock, lack of English, unemployment, discrimination, relationship with others and issues of identity. It argues for a three-pronged framework of acceptance, adaptation and adoption in facilitating integration. Thirteen Colombian refugees resettled from Ecuador took part in this research, who came to New Zealand between 2007 and 2014. Objective: This research seeks to explore the barriers that impact the integration of Colombian refugees in New Zealand. Also, to fill this gap in the literature by providing new knowledge on the subject already described. Methodology: The qualitative methodological approach of this study is an ethnographic collection of oral stories. Oral history interviews, a focus group and personal diaries were used as data collection methods. Results: The findings of this study show that Colombian refugees face challenges that put at risk their integration into New Zealand’s society, the main challenges faced by them are culture shock, lack of English, unemployment, discrimination, relationship with others and issues of identity. Conclusion: Despite the challenges already mentioned, the development of qualities such as acceptance, adaptation and adoption has contributed to overcoming these barriers and achieving their integration in New Zealand.